Modern principles of protected areas management: european experience - Demydenko, L. (Land Management, Cadastre and Land Monitoring, 2017)
The article outlines an understanding of the modern principles, types of management of protected areas and policies aimed at ensuring sustainable land use development taking into account European experience. The change in awareness of the role of nature in human life and place of man in the biological chain of the planet also changed the approaches to the creation of protected areas, measures of protection and management system and environmental and economic instruments of environmental land use. In Europe, there is an understanding that most of our biodiversity is found in semi-natural habitats that depend on long-term human management. This is reflected in the diversity of conservation policy types and strategies that have been developed in recent decades. Modern approaches recognize that well-managed nature conservation areas not only support important ecosystems and threatened species, but also provide many benefits to humans, including a range of ecosystem services. In practice, you can observe various types of management for protected areas. One of the forms of protected land use in Ukraine is the territory and objects of the nature reserve fund. Their successful use depends on a clear and coordinated management mechanism. Eurointegration processes in Ukraine (Association Agreement) require and the application of new approaches in the management of protected areas and the application of new principles for their creation, the use of ecological and economic incentives for management. Key words: nature conservation land use, protected areas, management principles, types of management.